PENGARUH E-SERVICE QUALITY TERHADAP E-SATISFACTION SERTA IMPLIKASINYA TERHADAP E-LOYALTY (STUDI PADA NASABAH BANK NEGARA INDONESIA (BNI) PENGGUNA MOBILE BANKING) - Andayani, Triya; Rommy, Nursaban; Nur, Nofal; Awasinombu, Aidin Hudani; Juharsah, Juharsah (Jurnal Manajemen dan Kewirausahaan, 2021)
The aims of the research are: (1). To determine the effect of e-service quality on e-satisfaction. (2). To determine the effect of e-satisfaction on e-loyalty. (3). To determine the effect of e-service quality on e-loyalty. (4). To determine the effect of e-service quality and e-satisfaction on e-loyalty. (5). To determine the effect of e-service quality on e-loyalty through e-satisfaction.Â  The population in this study is BNI Bank customers who use Mobile banking, while the number is unknown. The sample in this study were 104 respondents using purposive sampling method. The data collection method used in this study was an online questionnaire. The method of analysis using AMOS and SPSS.Â  The results of the study are: (1). E-service quality has a positive and significant effect on e-loyalty. (2). E-satisfaction has a positive but not significant effect on e-loyalty. (3). E-service quality has a positive and significant effect on e-loyalty. (4). E-service quality and e-satisfaction have a positive and significant effect on e-loyalty. (5). E-service quality has a positive but not significant effect on e-loyalty through e-satisfaction.